CFD simulation of gas-liquid hydrodynamics in aerated stirred tank - Azri, Abdullah (2010)
The aim of this work is to comparing the simulation result from Computational Fluid Dynamic (CFD) with the experimental measurement from Montante et al. (2007). Liquid axial velocity and liquid radial velocity were measured in order to get the similar result with experimental measurement from Montante et al. (2007). For this work, Gambit 2.4.6 and Fluent 6.3.26 software were use in modelling and running the simulation. The experimental results obtained at different gas flow rates are presented, compared with multi-phase data and discussed for gaining insight into the gas–liquid flows. The agreement between the experimental and the calculated mean velocity fields indicates that the selected CFD modelling is appropriate for the prediction of the mean hydrodynamic features of gas–liquid dispersions in stirred vessels.